IMPLEMENTATION OF LAW NUMBER 3 OF 2024 ON VILLAGES REGARDING THE ROLE OF VILLAGE GOVERNMENT IN COMMUNITY SERVICES AND THE IMPLEMENTATION OF VILLAGE DEVELOPMENT PROGRAMS IN BARENG VILLAGE, SEKAR DISTRICT, BOJONEGORO REGENCY: Implementasi Undang-Undang Nomor 3 Tahun 2024 Tentang Desa Terhadap Peran Pemerintah Desa Dalam Pelayanan Masyarakat Dan Pelaksanaan Progam Pembangunan Desa di Desa Bareng Kecamatan Sekar Kabupaten Bojonegoro - Fahimah Nurul Hidayah; Ernia Duwi Saputri; Heru Ismaya (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines decentralization under Law Number 3 of 2024 concerning Villages, which mandates the empowerment of village governments to enhance public services and implement development programs according to local needs. The research problem states how the implementation of Law Number 3 of 2024 concerning Villages affects the role of the village government in community service and the execution of development programs in Bareng Village, Sekar District, Bojonegoro Regency. The objective of the study is to identify the regulation’s implementation in the dimensions of community service and village development. A qualitative research method was chosen, employing observation, interviews, and documentation; data were analyzed through reduction, presentation, and verification. The findings indicate that the village’s authority in financial management and participatory planning has increased, accelerating the provision of administrative services and basic infrastructure. However, challenges arise in the synchronization of regulations across government levels and in strengthening the capacity of village officials. In conclusion, the implementation of Law 3/2024 has expanded the village’s role as a development subject, but its effectiveness depends on improved coordination and the competencies of the village government.